Partially Segmented Permanent-Magnet Losses in Interior Permanent-Magnet Motors - Jeremiah Vannest; Julia Zhang (Energies)
Permanent-magnet losses in interior permanent-magnet (IPM) motors can result in high magnet temperatures and potential demagnetization. This study investigates using partially segmented magnets as an alternative to traditional segmented magnets to reduce these losses. Partial segmentation involves cutting slots into the magnet to redirect the eddy current path and reduce losses. The research explores analytical and finite element modeling of eddy current losses in partially segmented magnets in IPM machines. Various configurations and orientations of partial segmentation were examined to assess their impact on eddy current losses. Axial slots for the partially segmented magnets were found to be the most effective slotting direction for the baseline IPM motor’s aspect ratio. This study also explores several methods for measuring permanent-magnet loss in IPM machines. A locked rotor test fixture was designed to measure losses induced by switching harmonics. AC loss measurements for the test fixture were conducted to compare magnets with and without partial segmentation. The results showed a significant reduction in permanent-magnet loss for the partially segmented magnets, particularly at higher currents and across all the tested switching frequencies and phase angles. Additionally, the transient temperature of the partially segmented magnets was found to be 12 °C lower than without partial segmentation after a 30 min test.